Socio-Emotional Behavior of Early Childhood in the Context of Play in the Bulo Neighborhood - Muh. Juliman, Aminasry; Yusuf, Munir; Subhan, Subhan (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
The development of socio-emotional behavior in early childhood is a crucial foundation for future social interaction and psychological well-being. This study aims to describe the forms of socio-emotional behavior in children aged 4ÔÇô5 within the context of play, identify influencing factors, and analyze the role of parents in supporting this development. A descriptive qualitative approach was used, with data collected through in-depth interviews and documentation involving 33 parents in the Bulo neighborhood, Walenrang Subdistrict, Luwu Regency. The findings indicate that most children demonstrated positive socio-emotional abilities, such as engaging in healthy interactions, independence, conflict resolution, and appropriate emotional expression. Key supporting factors include family environment, peer presence, quality of social interaction, and parental involvement in play activities. These results highlight the importance of synergy among families, communities, and educational institutions in creating a supportive and meaningful developmental environment for young children.